Plasma Levels of Growth Differentiation Factor 15 and Adverse Kidney Outcomes - Hee Byung Koh; Hyo Jeong Kim; Seok-Jae Heo; Cheol Ho Park; Hyung Woo Kim; Young Su Joo; Tae Ik Chang; Jung Tak Park; Tae-Hyun Yoo; Shin-Wook Kang; Seung Hyeok Han (Clinical Journal of the American Society of Nephrology, 2026)
Background: Growth differentiation factor-15 (GDF-15) has been implicated in adverse outcomes in cardiovascular disease and diabetes, highlighting its potential as a prognostic marker. However, its association with chronic kidney disease (CKD) development remains unclear. Therefore, we investigated the association between GDF-15 and incident CKD and explored potential causal mechanisms. Methods: We analyzed 31,965 UK Biobank participants without pre-existing CKD. The primary outcome was incident CKD, defined by diagnostic codes or an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m 2 (eGFR-based CKD). Proteomics-based mediation and protein-protein interaction analyses identified potential mediators linking GDF-15 to CKD. A bidirectional two-sample Mendelian randomization (MR) analysis using genome-wide association study summary statistics evaluated the potential causal relationship between GDF-15 and eGFR. Results: In multivariable cause-specific analyses, higher GDF-15 levels were significantly associated with increased CKD risk (hazard ratios: Q2, 1.05 [0.87-1.26]; Q3, 1.21 [1.01-1.45]; Q4, 1.87 [1.56-2.26] vs. Q1; P-for-trend